Dimensional Analysis under Linguistic Pythagorean Fuzzy Set - Villa Silva, Aldo Joel; Pérez Domínguez, Luis; Luviano Cruz, David; Martinez Gomez, Erwin Adan; Valles-Rosales, Delia Julieta (2021)
Dimensional analysis under linguistic Pythagorean fuzzy set (DA-LPFS) is a technique to handle qualitative (intangible) as well as the interactions between criteria, by combining dimensional analysis (DA) and Pythagorean fuzzy set (PFS) with linguistic variables. In this paper, a novel DA method is proposed for LPFSs based in a PFS extension, in order to consider the mutual relationship among criteria and handle qualitative (fuzzy) and quantitative (crisp) information usually involved in Multi-criteria decision making (MCDM) problems. Finally, DA-LPFS is applied to handle a case concerning the selection of CNC router to illustrate the applicability of the method.